CLASSROOM-BASED STUDY ON TEACHING PRONUNCIATION THROUGH SONGS - Amonova Nafisa; Zulfiya Axmedova (TADQIQOTLAR, 2026)
Annotation: This article explores a classroom-based study on teaching English pronunciation through songs, focusing on the effectiveness of integrating music into language learning environments. Pronunciation is a crucial component of communicative competence; however, it often poses challenges for learners due to differences in phonological systems, stress patterns, rhythm, and intonation. Traditional teaching methods may not always provide sufficient exposure to natural speech, which makes alternative approaches necessary. The study aims to investigate how songs can serve as an effective pedagogical tool to improve learners’ pronunciation skills in an engaging and meaningful way. Songs offer authentic language input, natural rhythm, repetition, and emotional engagement, which facilitate better retention and imitation of sounds. In this research, classroom activities such as listening tasks, singing along, phonetic analysis, and repetition exercises were implemented to enhance students’ pronunciation. The methodology of the study is based on a qualitative and quantitative approach, including classroom observations, pre- and post-tests, and student feedback. The participants were English language learners at an intermediate level. The results demonstrate that the use of songs significantly improves learners’ pronunciation accuracy, stress placement, and intonation patterns. Moreover, students showed increased motivation, confidence, and active participation during the lessons. The findings suggest that incorporating songs into pronunciation teaching not only makes the learning process more enjoyable but also creates a supportive environment for language acquisition. The study highlights the importance of selecting appropriate songs that match learners’ proficiency levels and linguistic needs. In conclusion, this research supports the integration of music- based activities as an effective and innovative approach in teaching English pronunciation in classroom settings.